Antenatal depression: Efficacy of a pre-post therapy study and repercussions in motor development of children during the first 18 months postpartum. Study: "Pregnancy care, healthy baby". (April 2022) - Pinheiro, Ricardo Tavares; Souza, Luciano Dias de Mattos; Trettim, Jéssica Puchalski; de Matos, Mariana Bonati; Pinheiro, Karen Amaral Tavares; da Cunha, Gabriela Kurz; Rubin, Bárbara Borges; Scholl, Carolina Coelho; Stigger, Rafaelle Stark; Motta, Janaína Vieira dos Santos; de Oliveira, Sandro Schreiber; Ghisleni, Gabriele; et al.
Abstract: Aims: To evaluate the efficacy of brief psychotherapeutic interventions of cognitive behavioral therapy to treat antenatal depression and verify the association between interventions and motor development of infants at 3 and 18 months of age. Methods: Pre-post-intervention study nested a randomized clinical trial, both of which are extracts from a population-based cohort study of a southern Brazilian city. The major depressive episode was measured through Mini Plus, the severity of depressive symptoms by BDI-II and motor development using Bayley-III and AIMS. The follow-ups occurred during the gestational period (T2) and at 3 (T3) and 18 months (T4) after delivery. Results: Data were analyzed from 336 women in the control group (not intervened) and 108 from the group of depressed women who received intervention for antenatal depression. The effectiveness of the interventions for a major depressive episode was around 80% for both models in the two follow-up stages (3 and 18 months postpartum). In addition, the children whose mothers received intervention presented 3.7 (95% CI 0.7–6.6) points higher in Bayley-III at 3 months old when compared to the children in the control group (p = 0.01). There was no difference between the two psychotherapy models tested, both being equally effective (p > 0.05). Conclusions: We found that the brief psychotherapeutic interventions of cognitive behavioral therapy for gestational depression were effective in causing remission of the condition both in the short and long term, besides indirectly causing benefits also to the children, with regard to their motor development. Highlights: CBT interventions are effective in the treatment of antenatal depression. CBT in pregnancy is associated with better motor development of children at 3 mths The addition of MI did not add to the efficacy for the antenatal depression.